(untitled) (REMUNOM, 2025)
This article analyzes the role of social media in situations involving domestic violence, delving into the positive and negative effects of this exposure. It is observed that, although presented as a tool for reporting, reporting, and empowering women, social media can become a space for public judgment and, in some cases, revictimization. Therefore, the question arises at what point the digital environment will cease to be an environment that effectively contributes to combating domestic violence and begin to contribute to further harm to the victim. Given the growing influence of the media on society’s perception of gender-based violence, as well as the visibility generated by reporting, this topic becomes urgent and relevant for legal and social debate. The research adopted is bibliographical in nature, conducted through the analysis of widely publicized concrete cases, as well as scientific articles and applicable legislation. It is concluded that social networks play an ambiguous role: functioning as a tool for reporting and mobilization, but also exposing victims to new forms of revictimization by society, making it necessary to analyze how these issues should be approached in order to avoid additional harm and promote effective and responsible awareness.